WRITING THE SCRIPT OF NATIVE ADVERTISING VIDEO FOR TAJUNGAND BLONGSONG CLOTHS - Muhammad Nadjmuddin; Sunani Sunani; Indri Ariyanti; Muhammad Akbar Zamzami; Reza Novitasari; Zainab Tri Oktarya (HOLISTICS, 2019)
This study aims to investigate(1)how the video scriptsofnative advertising for promoting Tajung and Blongsongas Palembang traditional textile is made. (2) to what extend the video script made in the video of Tajung and Blongsong cloths fulfill the criteria of SPEAKING Model, (3) to what extend the video script made for the video of Tajung and Blongsong cloths fulfill the communicative functionsof the movestructure. Dell Hymes’ SPEAKINGModel and Bathia’s Move Analysis wereused for testing product advertising effectivenessThe results showed that the video script should be developed through several testing to validate the data. Furthermore, the analysis of the components of communication, and linguistic function revealed the video fulfilled the criteria for native advertising.